Storage temperature and quality of red mombin fruits (Spondias purpurea L.) - Kohatsu, Douglas Seijum; Zucareli, Valdir; Brambilla, Wilian Polaco [UNESP]; Evangelista, Regina Marta [UNESP]; Ono, Elizabeth Orika [UNESP]; da Silva, Tiago Roque Benetoli (My University, 2011)
The aim was to study the effect of different storage temperatures on quality of red mombin fruit. The red mombin fruits were obtained from the Company CEAGESP/Sao Paulo/Brazil and transported in cool boxes to the laboratory, where they were selected on the base of appearance, maturity lack of physical damage, sanitized in 50 ppm chlorine-free solution and packaged in polystyrene trays wrapped with film of polyvinyl chloride (PVC). The experiment was a completely randomized design with three temperatures (4, 8 and 25oC) and 5 time intervals (0, 2, 4, 6 and 8 days after the experiment installation). In each survey firmness, titratable acidity, soluble solids, ascorbic acid content, the skin color and also the release of CO2 by the fruit over time were evaluated. It was observed that low temperatures prolong the fruits shelf life and the storage temperature influences the characteristics, the temperature of 8oC was most suitable for the storage of red mombin fruits. Besides, the fruit color was a good indicator of changes in the pulp during storage.
Keywords: Anacardiaceae; Postharvest; Tropical fruits